The System of German consonants and specifics of their articulation (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article deals with the consonant system in German, which are divided by method of articulation in four groups and are the articulate base in German language. In the research the articulation of the consonants is considered as well.
Keywords: phonetics; German; consonant system; articulation; phonemes